Anthropocene invasion of an ecosystem engineer: resolving the history of Corophium volutator (Amphipoda: Corophiidae) in the North Atlantic. (19th March 2015) - Einfeldt, Anthony L.; Addison, Jason A.
Abstract : Resolving the natural histories of species is important for the interpretation of ecological patterns, as it provides evolutionary context for the interactions between organisms and their environment. Despite playing an integral role on the intertidal mudflats of the North Atlantic as an abundant food source for predators and as an ecosystem engineer that alters the soft sediment environment, no previous studies have provided empirical evidence to determine the biogeographical origin of the amphipod Corophium volutator . To resolve its status as introduced or indigenous in Europe and North America, we analyzed sequence data for two mitochondrial loci and two nuclear markers, aiming to determine whether the present range of C. volutator is the result of unresolved taxonomy, persistence in glacial refugia, natural trans‐Atlantic dispersal, or human‐mediated introduction. Our results demonstrate a reduced genetic diversity in North American populations that is a subsample of diversity in European populations, with coalescent analyses of mitochondrial and nuclear DNA supporting different models of multiple introductions from Europe to the Bay of Fundy and Gulf of Maine in North America. These results suggest that C. volutator was introduced to North America prior to the first surveys of local biota in the 20th Century, which has broad implications for interpretations of community and ecosystem interactions in the North Atlantic intertidal. © 2015 The Linnean Society of London, Biological Journal of the Linnean Society, 2015, 115, 288–304.